Optimization of Bentonite Thermal Activation for Reducing Fe Metal and Organic Substance in Peat Water - Hidayat, Ali Nurdin; Permana , Edwin; Wijaya , Dhian Eka (Journal of Community Based Environmental Engineering and Management, 2025)
Peat water is water produced from decaying trees and plants that contain Fe metal with a high content of organic substances. Therefore, effective and efficient peat water treatment is needed to make it suitable for consumption. Bentonite is a natural source of adsorbent but has a fairly low adsorption activity, so bentonite needs to be activated to increase its adsorption ability. Thermal activation was chosen due to its environmentally friendly process and can increase the surface area and adsorption ability of bentonite. This study was conducted to see the effect of bentonite thermal activation with temperatures of 200, 300, 400 and 500˚C in reducing Fe metal content, organic matter, TDS and pH of peat water. The results show that thermal activation of bentonite can reduce the content of these compounds. Thermal activation of bentonite at 500˚C reduced Fe metal content with 66% efficiency and 0.08 mg/g adsorption capacity, 89.6% organic matter with 24,60 mg/g adsorption capacity and TDS 27 mg/l.